Analysis of mixed adhesive joints considering the compaction process. (July 2017) - Chiminelli, Agustín; Breto, Rubén; Izquierdo, Salvador; Bergamasco, Luca; Duvivier, Emmanuel; Lizaranzu, Miguel
Abstract: Incorporating a material properties variation along the bondlines has proved to be a useful method for improving adhesive joints performance. In this work, the potential of the technique is analysed for a single lap joint using the mixing adhesives approach. In order to include the compaction process effect in the structural analysis during the joint assembly, a computational fluid-dynamic model capable of integrating different resins along the bondline has been developed. Then, the results obtained from this model are mapped into a finite element model through an application developed for this purpose. Several parametric studies have been carried out comparing different configurations in terms of maximum load capacity of the joints. Finally, one of these joints configurations has been manufactured using a special device developed for assembling these mixed adhesive joints and tested. This banded configuration have shown both numerically and experimentally an ultimate load improvement of over 70%.